Novel iron complexes with quinoxaline N-1,N-4-dioxide derivatives: synthesis, characterization and antimycobacterial activity - Tarallo, M. Belen; Urquiola, Carolina; Monge, Antonio; Pavan, Fernando R. [UNESP]; Leite, Clarice Q. [UNESP]; Torre, Maria H.; Gambino, Dinorah; Collery, P.; Maymard, I; Theophanides, T.; Khassanova, L.; Collery, T. (John Libbey Eurotext, 2008)
Three new iron complexes with 3-aminoquinoxaline-2-carbonitrile N-1, N-4-dioxide derivatives (L) with stoichiometries [Fe(L1)(2)], [Fe(L1)(3)] and [Fe(L2)(3)]center dot 5H(2)O were synthesized and characterized. Both ligands and complexes showed in vitro activity against Mycobacterium. tuberculosis H(37)Rv (ATCC 27294) (MIC=3.9 mu g/mL for [Fe(L1)(2)] and [Fe(L2)(3)]center dot 5H(2)O and 7.8 mu g/mL for [Fe(L1)(3)]) with low citotoxicity. Two of the three complexes presented better activity than the free ligands, demonstrating that metal coordination can favorably modify the profile of antimycobacterial activity of 3-aminoquinoxaline-2-carbonitrile N-1,N-4-dioxide derivatives.
Keywords: M. tuberculosis; quinoxaline N-1,N-4-dioxides; iron complexes